Molecular docking of rutenum complex with epiisopyloturin and nitric oxide against nucleoside diphosphate kinase protein Leishmania (Research, Society and Development, 2020)
Leishmaniasis is an infectious disease that affects both animals and humans, caused by flagellated parasites belonging to the genus Leishmania may present in different clinical forms depending on the infecting strain and the immune reaction of the host. The disease is estimated to reach about 700,000 to 1 million people, causing the deaths of 20 to 30,000 individuals annually. Thus, the present study aims to perform a molecular coupling simulation of the ruthenium complex with epiisopiloturin and nitric oxide against the protein Nucleoside diphosphate kinase from Leishmania amazonensis. The NDK 3D molecule was extracted from the PDB nucleic proteins and acids database. The 3D molecular structure of the Epiruno2 complex was designed using gaussview 5.0 software. The NDK target and Epiruno2 complex were prepared for docking simulations, where NDK was considered rigid and Epiruno2 was considered flexible. The Epiruno2 complex presented a good molecular affinity rate with the target protein, making it attractive for experimental trials in laboratories for Leishmania's NDK protein and NDKs of other pathogens, however, the drug miltefosin presented low molecular affinity for the same target, corroborating studies presented in the literature on the reduced efficacy of current drugs against leishmaniosis.